2020
DOI: 10.1007/s40145-020-0381-x
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Er3+ and Yb3+ co-doped SrZrO3 nanocrystals under near-infrared and near-ultraviolet excitations

Abstract: In this study, the upconversion (UC) emissions of Er3+ and Yb3+ co-doped SrZrO3 nanocrystals (NCs) were investigated in terms of the thermal annealing temperature and concentration of Er3+ ions and compared with the emissions under a near-ultraviolet (near-UV) excitation. The NCs were synthesized by the combustion method, and the as-synthesized NCs were post-annealed at high temperatures. The X-ray diffraction patterns revealed that the grain sizes and crystallinity degrees of the samples increased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Therefore, suppression of surface quenching of NCs is an effective fluorescence enhancement method. A core–shell nanostructure is widely used to enhance fluorescence by protecting the RE 3+ in the core from nonradiative decay due to surface defects. , Another way to reduce surface defects is high-temperature annealing using a calcination furnace, which can increase the particle size of NCs to reduce the surface-to-volume ratio and leads to an enhanced UC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, suppression of surface quenching of NCs is an effective fluorescence enhancement method. A core–shell nanostructure is widely used to enhance fluorescence by protecting the RE 3+ in the core from nonradiative decay due to surface defects. , Another way to reduce surface defects is high-temperature annealing using a calcination furnace, which can increase the particle size of NCs to reduce the surface-to-volume ratio and leads to an enhanced UC …”
Section: Introductionmentioning
confidence: 99%
“…26,27 Another way to reduce surface defects is hightemperature annealing using a calcination furnace, which can increase the particle size of NCs to reduce the surface-tovolume ratio and leads to an enhanced UC. 28 Recently, it has been found that laser annealing can greatly enhance fluorescence by changing the crystal phase, 29 enlarging the particle size, 30 and enhancing energy transfer efficiency. 31 For example, Bednarkiewicz et al found that 2 mol % Er 3+ /20 mol % Yb 3+ :NaYF 4 nanoparticles could recrystallize to different phases and exhibit large 2−3 order enhancement in fluorescence via laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice of matrix material not only affects the dopant's optical transition, but also reduces its excitation energy [18]. Among various matrix materials, phosphate has a wide band gap and high efficiency, with high thermal stability and chemical durability [19,20]. Silicate has been widely studied as a satisfactory matrix for fluorescent materials due to its excellent optical properties, chemical stability, and structural diversity [21,22].…”
Section: Introduction mentioning
confidence: 99%
“…14 Another method of reducing surface defects is to anneal the material at high temperature, which can increase the size of nanoparticles, reduce the surface-to-volume ratio, and enhance UC. 15 By comparison, doping is a simple and effective strategy to significantly improve its luminescence properties by regulating the lattice and electronic symmetry of phosphor substrates. The typical examples are that the UC luminescence could be enhanced by doping metal ions (small-atomic-radius Li + , Na + and K + , or transition-metal-ions Mn 2+ , Ni 2+ , and Cu 2+ , or other metal-ions Bi 3+ and so on).…”
Section: Introductionmentioning
confidence: 99%